Synthesis and characterization of poly(vinylchloride) type macrophotoinitiator comprising side-chain thioxanthone via click chemistry (eXPRESS Polymer Letters, 2011)
Nowadays, the use of macromolecular photoinitiators provides for a good compatibility of the initiator in the formulation. Moreover, the migration of the initiator to the surface of the material is prevented, which results in low-odor and non-toxic coatings. In the present study, it has been demonstrated that polyvinylchloride macrophotoinitiator (PVC-TX) containing side chain thioxanthone (2%) moieties were successfully prepared by 'click chemistry'. For this purpose, propargyl thioxanthone and polyvinylchloride with side chain azide moieties were reacted in N,N-dimethylformamide for 24 hours at 25°C in order to give corresponding macrophotoinitiator. The synthesized polymer was characterized by 1H-NMR (nuclear magnetic resonance), UV (ultraviolet) and fluorescence spectroscopies and water based gel permeation chromatography. Obtained macrophotoinitiator has similar absorption characteristics compared to parent thioxanthone. Its capabilities to act as initiator for the photopolymerization of methacrylic acid, methyl methacrylate, N-vinyl pyrrolidone and styrene in various solvents in the absence and presence of triethylamine media were also examined.